Spotlighting Women-Led Fisheries Livelihoods Toward Sustainable Coastal Governance: The Estuarine and Mangrove Ecosystem Shellfisheries of West Africa - Chuku, Ernest Obeng; Effah, Elizabeth; Adotey, Joshua; Abrokwah, Sika; Adade, Richard; Okyere, Isaac; Aheto, Denis Worlanyo; Kent, Karen; Osei, Isaac Kofi; Omogbemi, Emmanuel Dami; Adité, Alphonse; Ahoedo, Kossi; et al. (Frontiers in Marine Science, 2022)
The governance of coastal and marine resources remains a complex socioecological endeavor in many African countries but women are leading the way and demonstrating a pathway for food fish security through rights-based co-management of shellfisheries in estuarine and mangrove ecosystems in West Africa. We report comprehensively, for the first time, the scale of estuarine and mangrove ecosystem-based shellfisheries (EMES) across the West African coast (Senegal, Gambia, Guinea Bissau, Guinea, Sierra Leone, Liberia, Côte d’Ivoire, Ghana, Togo, Benin, and Nigeria), the gender dynamics, and implications for the sustainable management of this small-scale fishery. We find an extensive geographical coverage of active shellfisheries within these ecosystems with close to 571,000 household beneficiaries and over 50,000 harvesters, mainly women, being the primary resource users. An annual shellfish harvest of over 300,000 MT valued at USD 336 million is potentially undocumented across the region. Harvested shellfish species of economic importance comprised 18 species of mollusks, 11 species of crustaceans, and a few unidentified groups of gastropods, crustaceans, and cephalopods. The West African mangrove oyster, periwinkle, bloody cockle, whelk, and razor clam were, in that order, the most harvested shellfish. The bivalve and gastropod value chains are dominated by women harvesters at all nodes whereas women play significant roles in the processing and marketing of crustacean and cephalopod fisheries. Formal laws specific to the regulation of estuarine shellfisheries are generally nonexistent, however, the organized women shellfish harvester groups of the Tanbi wetlands (The Gambia) and Densu Delta (Ghana) have championed sustainable governance actions resulting in successful women resource user-led fisheries co-management. The elements of success and opportunities for scaling up these examples are discussed. The presence of such groups in several locations offers an entry point for replicating a similar co-management approach across the West African coast.